Pregnancy Outcome in Women With Familial Mediterranean Fever: A Retrospective Analysis of 50 Cases With a 10-Year Experience - Aslıhan YAZICIOĞLU; Mert TURGAL; Özge Senem YÜCEL; Özgür ÖZYÜNCÜ; M. Sinan BEKSAÇ (Archives of Rheumatology, 2014)
Objectives: Since little is known about perinatal outcome of patients with familial Mediterranean fever (FMF), we report our clinical experience about pregnant women with FMF in this study. Patients and methods: Fifty pregnant women (mean age 29.5 years; range 19 to 39 years) with FMF were enrolled between January 2002 and December 2012. Patient data were collected from computerized database. Clinical characteristics including demographics, pregnancy outcome, maternal and fetal complications during pregnancy or delivery, hypercoagulation disorders and colchicine use were recorded. Labor patterns and perinatal outcomes were assessed. Results: The mean gestational week at delivery was 36.3. Maternal complications were encountered in two patients including hemodialysis associated sepsis and cerebrovascular accident. We did not encounter FMF attacks in the course of pregnancies. A total of 42 patients (84%) were on drug therapy of colchicine. Two congenital anomalies were encountered, one was tanatrophic dysplasia (on colchicine therapy) and the other was an open type neural tube defect (not on colchicine therapy). Patients were also searched for thrombophilias and 15 (30%) had positive test result. The course of the pregnancy was free of venous complications with low molecular weight heparin prophylaxis. Preterm delivery, low birth weight and congenital anomalies were not significantly associated with colchicine therapy. Conclusion: A favorable pregnancy and perinatal outcome may be expected in patients with FMF treated with colchicine. However, close followup with prenatal test and laboratory investigations for maternal and fetal well-being including hypercoagulation disorders are thought to be essential.